Crypto-compression scheme based on the DWT for medical image security. (1st August 2019) - Abdmouleh, Med Karim; Khalfallah, Ali; Bouhlel, Med Salim
Ensuring the confidentiality of exchanged data is always a great concern for any communication. Also, the purpose of compression is to reduce the amount of data while preserving important information. This reduction leads to the archiving of more information on the same storage medium and minimises the transfer times via telecommunication networks. Indeed, the combination of encryption and compression guarantees both confidentiality and authentication of information. In addition, it reduces processing time and transmission on public channels and increases storage capacity. In this paper, we propose a new approach of a partial or selective encryption for medical Images based on the discrete wavelet transform (DWT) coefficients and compatible with the norm JPEG2000. The obtain results prove that, the proposed scheme provides a significant reduction of the processing time during the encryption and decryption, without tampering the high compression rate of the compression algorithm.